Model Pengembangan Kompetensi Pedagogik Guru Di Lingkungan Sekolah Dasar Negeri 267 Griya Bumi Antapani Kota Bandung - Deddy Sukmana (Ridwan Institute, 2021)
This research aims to develop pedagogical competency models of teachers in the public elementary school 267 Griya Bumi AntapaniBandung. This research uses qualitative method with its exposure technique using descriptive technique. The data collection techniques use interview methods, questionnaires, and documentation studies. Based on the results, the results were obtained that the ability of teachers at SDN 267 is still low in the competency of assessment and evaluation of learning processes and outcomes as well as the making of Class Action Research. The solution to improve the pedagogical competence of teachers at SDN 267 Griya Bumi Antapani Bandung through an effective and innovative development model, namely the Incubation Program with peer coaching method. The implementation of its activities with an In-On-In pattern. The mentoring technique is carried out with online and offline techniques (Blended Learning) by utilizing information and communication technology in accordance with the current digital era.